2002
DOI: 10.1002/jemt.10225
|View full text |Cite
|
Sign up to set email alerts
|

Supraspinal connections of the ovary: Structural and functional aspects

Abstract: This review summarizes our recent studies using the viral transneuronal tracing technique to identify sites in the central nervous system (CNS) that are connected with the ovary. A neurotropic virus (pseudorabies virus) was injected into the ovary and various times after the inoculation the spinal cord and brain were examined for virus-infected neurons identified by immunocytochemistry. Such neurons could be detected in well-defined cell groups of the spinal cord (intermediolateral cell column), brain stem (va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 81 publications
1
30
0
Order By: Relevance
“…The majority of cerebral cell groups we found labeled are known to have direct synaptic contact with the sympathetic or parasympathetic preganglionic neurons and/or the vagal nuclei (for details and references, see Gerendai et al, 2002).…”
Section: Distribution Of Virus-infected Neuronsmentioning
confidence: 99%
“…The majority of cerebral cell groups we found labeled are known to have direct synaptic contact with the sympathetic or parasympathetic preganglionic neurons and/or the vagal nuclei (for details and references, see Gerendai et al, 2002).…”
Section: Distribution Of Virus-infected Neuronsmentioning
confidence: 99%
“…The rise in LH can already be seen 3 min after ejaculation (13). Spontaneous ovulatory animals with also the potential to induce a reflex ovulation (facultative reflex ovulators), like rats, have autonomic nerves (parasympathetic and sympathetic) and visceral sensory fibers innervating the ovary (14,15). Copulation in the spontaneous ovulating rats can trigger or hasten ovulation and cervicovaginal stimulation increases the output of eggs (12,16).…”
Section: Neuronal Pathwaysmentioning
confidence: 99%
“…Copulation in the spontaneous ovulating rats can trigger or hasten ovulation and cervicovaginal stimulation increases the output of eggs (12,16). Furthermore, it seems that the ovarian nerves can influence the hormonal activity and interfere with cyclicity (14). Transsection of the efferent parasympathetic fibers in rats (vagotomy) altered the length of the estrous cycle (17) and caused a delay of the onset of puberty (18).…”
Section: Neuronal Pathwaysmentioning
confidence: 99%
“…The vagus nerve is one of the neural pathways involved in regulating ovarian functions [1-9] Gerendai and collaborator's provided the first morphological evidence of a multi-synaptic neural pathway between the ovary and the central nervous system (CNS), showing that the vagus nerve forms part of such neural connection [6,7,10]. Unilateral ovariectomy (ULO) is an experimental tool used to analyze the existence of functional asymmetry between the ovaries.…”
Section: Introductionmentioning
confidence: 99%
“…Burden and Lawrence [1] suggested that the ovarian innervation modulates ovarian functions. Ample experimental evidence supporting the idea that ovarian functions are modulated by at least two different neural pathways, the noradrenergic system (via the superior ovarian nerve and the ovarian plexus) and the parasympathetic system (via the vagus nerve), have been published [6,7,9,17-23]. …”
Section: Introductionmentioning
confidence: 99%